2004
DOI: 10.1007/s00737-004-0047-7
|View full text |Cite
|
Sign up to set email alerts
|

Can gender differences in the prevalence of mental disorders be explained by sociodemographic factors?

Abstract: Overall the emotional advantages or disadvantages of marital status, employment status, number of children, parenthood and social class apply equally to men and women. We cannot explain the female preponderance in most mental disorders by detecting specific unfavourable patterns of sociodemographic correlates, suggesting that determinants of gender differences in common mental disorders are still far from being understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
3
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(104 citation statements)
references
References 82 publications
8
82
3
8
Order By: Relevance
“…The three 11-min/trial OSST was not sufficient to induce an increased immobility over trials in the males but was strong enough to trigger the increased depressive behavior over trials in the females. This observation is consistent with the report that the female preponderance in depression cannot be explained by sociodemographic factors (Klose and Jacobi, 2004). Furthermore, our results show that the higher female vulnerability fluctuates across estrous cycle stages and is, at least partially, mediated by the sex hormones.…”
Section: Discussionsupporting
confidence: 93%
“…The three 11-min/trial OSST was not sufficient to induce an increased immobility over trials in the males but was strong enough to trigger the increased depressive behavior over trials in the females. This observation is consistent with the report that the female preponderance in depression cannot be explained by sociodemographic factors (Klose and Jacobi, 2004). Furthermore, our results show that the higher female vulnerability fluctuates across estrous cycle stages and is, at least partially, mediated by the sex hormones.…”
Section: Discussionsupporting
confidence: 93%
“…(Nakao et al, 2001). 5 Similarly, another study reported that being single, separated, divorced or widowed women, compared to married women is associated with a significantly increased likelihood of any mental disorders, except for somatoform disorder (s) (Klose and Jacobi, 2004). 7 In present study, somatoform disorder in widower and separated was having clear severity over its counterparts and therefore our study bridged the untouched area in this realm as well.…”
Section: Marital Statussupporting
confidence: 60%
“…5 Similarly, another study reported that being single, separated, divorced or widowed women, compared to married women is associated with a significantly increased likelihood of any mental disorders, except for somatoform disorder (s) (Klose and Jacobi, 2004). 7 In present study, somatoform disorder in widower and separated was having clear severity over its counterparts and therefore our study bridged the untouched area in this realm as well. Interestingly, Kismayer et al 8 found a lower risk of somatoform disorder in unmarried than in married subjects; this is in parallel with our observations of the present study, wherein those who were widow/widower have shown the highest suffering tendency as far as mean BSI scores for somatoform disorders were concerned (range= 44.74 to 46.62).…”
Section: Marital Statussupporting
confidence: 60%
“…Ancak yaş ilerledikçe kadın ile erkek arasındaki bu fark azalmaktadır. Depresif bozukluklar yaşamları süresince erkeklerin %5-12'sini, kadınların ise %10-25'ini etkilemektedir (15). MDB'nin kadınlarda erkeklerin 2 katı olmasının nedenleri olarak hormonal farklılıklar, genetik duyarlılık ya da MAO yüksek-liği ve tirod hastalıkları, menstruasyon gibi biyolojik etmenler yanında, çocukluğundan itibaren şiddete maruz kalma, girişken olma yönünden baskılanma, boyun eğen, pasif ve bağımlı olmayı öğrenme, kadına verilen toplumsal roller ve ondan beklentiler (ev işleri, çocuk doğurma, çocuk yetiştirme, eşe karşı sorumluluklar), düşük eği-tim ve gelir olanakları, işsizlik, düşük sosyoekonomik düzey, ayrımcılığa maruz kalma gibi riskler gösterilmektedir (13,14,(16)(17)(18)(19).…”
Section: Major Depresi̇f Bozukluk Epi̇demi̇yoloji̇si̇unclassified